2005
DOI: 10.1104/pp.104.054502
|View full text |Cite
|
Sign up to set email alerts
|

Partial Reconstruction of Flavonoid and Isoflavonoid Biosynthesis in Yeast Using Soybean Type I and Type II Chalcone Isomerases  

Abstract: Flavonoids and isoflavonoids are major plant secondary metabolites that mediate diverse biological functions and exert significant ecological impacts. These compounds play important roles in many essential physiological processes. In addition, flavonoids and isoflavonoids have direct but complex effects on human health, ranging from reducing cholesterol levels and preventing certain cancers to improving women's health. In this study, we cloned and functionally characterized five soybean (Glycine max) chalcone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
204
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 47 publications
10
204
0
2
Order By: Relevance
“…Both QRT-PCR assays and promoter-report expression studies suggested that the plants activated the MtFNSII-2 gene that was normally expressed in other tissues, rather than boosting the constitutively root-expressed MtFNSII-1. One possible reason for this choice could be the coordinate activation of biosynthetic pathway enzymes upon defense (nodulation) signals (Ralston et al, 2005). Enzymes that form a complex together are coordinately regulated to enable proper channeling of metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both QRT-PCR assays and promoter-report expression studies suggested that the plants activated the MtFNSII-2 gene that was normally expressed in other tissues, rather than boosting the constitutively root-expressed MtFNSII-1. One possible reason for this choice could be the coordinate activation of biosynthetic pathway enzymes upon defense (nodulation) signals (Ralston et al, 2005). Enzymes that form a complex together are coordinately regulated to enable proper channeling of metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo yeast assays were carried out as previously described with minor modifications (Ralston et al, 2005). Yeast cultures (2 mL) were grown overnight at 30°C in appropriate SD dropout liquid media (CLONTECH) containing 2% (w/v) Glc.…”
Section: Est Sequence Analysis and Cloning Of Mtfnsii-1 And Mtfnsii-2mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of GmFNSII were only approximately one-fifth of the expression of F3H in the vector-control hairy roots. However, since both the genes showed tissue-specific expression patterns and differential transcript levels in all the tissues (Ralston et al 2005;Jiang et al 2010), it was not possible to speculate whether the results would be repeated if different tissues were tested in transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the genes encoding each of these enzymes have been identified (Steele et al 1999;Zabala and Vodkin 2005;Jiang et al 2010). Ralston et al (2005) described the RNA interference (RNAi) of soybean isoflavone synthase genes using the soybean cotyledon system, and this led to enhanced plant susceptibility to Phytophthore sojae in hairy roots. Jiang et al (2010) suggested that RNAi-mediated suppression of isoflavone synthase pathway genes could enhance isoflavone production in soybean.…”
Section: Introductionmentioning
confidence: 99%